2009
DOI: 10.1016/j.canlet.2008.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Hexachlorophene suppresses β-catenin expression by up-regulation of Siah-1 in EBV-infected B lymphoma cells

Abstract: Many studies have shown that the activation of beta-catenin signaling can promote oncogenesis, and it is therefore of interest to find agents that modulate this pathway. Recent work has shown using B lymphoma cells that infection by Epstein-Barr virus (EBV) and expression of its latent membrane protein (LMP)-1, cause increases in the expression of beta-catenin and cellular transformation. Conversely, results from cell-based small molecule screening studies have shown that the antibiotic hexachlorophene can dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The Wnt/β-catenin pathway is also significantly involved in the progression of numerous types of carcinomas, including leukemia, myeloma (16)(17)(18)(19) and several subtypes of lymphoma (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). It is known that activation of the Wnt/β-catenin pathway could be important for malignancy of DLBCL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Wnt/β-catenin pathway is also significantly involved in the progression of numerous types of carcinomas, including leukemia, myeloma (16)(17)(18)(19) and several subtypes of lymphoma (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). It is known that activation of the Wnt/β-catenin pathway could be important for malignancy of DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt/β-catenin pathway plays an important role in the progression of leukemia, myeloma (16)(17)(18)(19) and several subtypes of lymphoma, such as Epstein-Barr virus (EBV)-positive Burkitt's lymphoma (BL) (20)(21)(22), mantle cell lymphoma (MCL) (23)(24)(25), cutaneous lymphoma (26), extranodal marginal zone lymphoma (27), ALK-positive anaplastic large cell lymphoma (28), small B-cell lymphoma (29) and DLBCL (9,30). Scientists demonstrated that ethacrynic acid (EA) and the antifungal agent ciclopirox olamine (cic) inhibited the Wnt/β-catenin signaling in OPM-2 myeloma and three lymphoma cell lines (OCI-LY8-LAM-53, SU-DHL-4 and Raji) in vitro, leading to apoptosis and a significant decrease in the viability of lymphoma and its cell lines (30).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a large proportion of B-LPDs show a limited response to chemotherapy. To explore the relevance of PAX5 for drug resistance in B-LPDs, the PAX5-positive IM9 cell line was used as a representative PAX5-positive malignant B-cell line (Brien et al, 2007;Chu et al, 2014;Davis et al, 2010;Min et al, 2009;Shimizu et al, 2006). U266 and RPMI8226 cell lines were employed as PAX5-null multiple myeloma cell lines, and the Daudi cell line was used as a PAX5-positive Burkitt's-lymphomaderived B-lymphoblast representative (Fig.…”
Section: Pax5-positive Cells Are More Resistant To Chemotherapy Drugsmentioning
confidence: 99%
“…Next, to address the possibility that the expression levels of β-catenin are directly related to the proliferation of pancreatic cells, hexachlorophene (an inhibitor of β-catenin that was used for our previous study; Min et al, 2009), was used to treat Panc-PAUF and Bx-ConshRNA cells. As seen in Figure 4C, inhibition of β-catenin expression with hexachlorophene suppressed both cell lines despite the presence of PAUF (P < 0.01).…”
Section: Pauf Activates Akt-gsk3β Signaling Via a Unique Pattern Of Pmentioning
confidence: 99%